Zakonodajna dejavnost na področju socialne varnosti - Mišič, Luka (Delavci in delodajalci, 2023)
Starting from the recently enacted, but later suspended Long- Term Care Act, the paper discusses the most important aspects of legal drafting in the field of social security. It deals with aspects that the legislator, if he wants to ensure both a dynamic as well as a constitutionally sound development of the field, must not overlook. The Long-Term Care Act, which represents the most important new piece of legislation in the field of social security in the last decade and which will crucially co-shape the future of the Slovenian social security system and the legal and factual or socio-economic position of insured persons, was drafted in a regulatory hurry. For the sake of speed concerning the legislative process, some of the key dogmatic and constitutional principles were clearly sacrificed.
Keywords: basic principles; Dolgotrajna oskrba; legal drafting; long-term care; Long-Term Care Act; Slovenija; social security; Socialna varnost; temeljna načela; Zakon o dolgotrajni oskrbi; zakonodajna dejavnost